1990
DOI: 10.2337/diab.39.6.757
|View full text |Cite
|
Sign up to set email alerts
|

Vanadate Induction of Pancreatic Amylase mRNA in Diabetic Rats

Abstract: Amylase activity and mRNA abundance are reduced to < 1 % of normal levels in diabetic rat pancreas. Administration of vanadate in drinking water restored normal amylase activity and amylase mRNA levels. These results demonstrate an effect of vanadate on pancreatic acinar cells and suggest that vanadate can mimic the effect of insulin on transcription of the pancreatic amylase gene. Diabetes 39:757-59,1990 I norganic vanadate has the remarkable property of reproducing several of the biological effects of insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Bosch et al [34] have found that vanadate inhibits the expression of transfected chimeras of PEPCK in both FTO-2B and H4IIE rat hepatoma cells. In adult rat hepatocytes in primary culture, vanadate in the presence of glucose induced L-type pyruvate kinase mRNA [35], and in a streptozocin-induced diabetic rat vanadate was found to increase pancreatic amylase mRNA [36]. In a similar light, oral administration of selenate to diabetic animals partly reversed abnormal liver expression of both glycogenic and gluconeogenic enzymes [37].…”
Section: Insulin and The Insulin-mimetic Action Of Selenate On Glucosmentioning
confidence: 70%
“…Bosch et al [34] have found that vanadate inhibits the expression of transfected chimeras of PEPCK in both FTO-2B and H4IIE rat hepatoma cells. In adult rat hepatocytes in primary culture, vanadate in the presence of glucose induced L-type pyruvate kinase mRNA [35], and in a streptozocin-induced diabetic rat vanadate was found to increase pancreatic amylase mRNA [36]. In a similar light, oral administration of selenate to diabetic animals partly reversed abnormal liver expression of both glycogenic and gluconeogenic enzymes [37].…”
Section: Insulin and The Insulin-mimetic Action Of Selenate On Glucosmentioning
confidence: 70%